2019
DOI: 10.4028/www.scientific.net/jbbbe.41.11
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Curvature and Lower Extremities Kinematics of Simulated Pregnancy during Stair Ascending and Descending

Abstract: The purpose of this work is to investigate the effect of anteriorly-added mass to simulate pregnancy on lower extremities kinematic and lumbar and thoracic angles during stair ascending and descending. 18 healthy females ascended and descended, with and without a pseudo-pregnancy sac of 12 kg (experimental and control groups, respectively), a costume-made wooden staircase while instrumented with 20 reflective markers placed on the lower extremities and the spine. The movements were captured by 12 infrared came… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…The results of their study showed that when participants were asked to carry a 20% unilateral (asymmetrical) external loads during stair ascent, they demonstrated a significant increase in moment magnitudes of trunk bend, hip abduction, and external knee varus [15]. The impact of postural stability and balance control, while moving with an external loads, has been reported to overall intensification in center of pressure projection and sway speed thus requiring greater effort to maintain balanced moving patterns [17][18][19]. In summary, the task of stair ascending whiles carrying an external load increases the demands to maintain stability.…”
mentioning
confidence: 99%
“…The results of their study showed that when participants were asked to carry a 20% unilateral (asymmetrical) external loads during stair ascent, they demonstrated a significant increase in moment magnitudes of trunk bend, hip abduction, and external knee varus [15]. The impact of postural stability and balance control, while moving with an external loads, has been reported to overall intensification in center of pressure projection and sway speed thus requiring greater effort to maintain balanced moving patterns [17][18][19]. In summary, the task of stair ascending whiles carrying an external load increases the demands to maintain stability.…”
mentioning
confidence: 99%